Scarification in no-tillage: soil physics and plant development - Prazeres, Marco Segalla; Barbosa, Fabrício Tondello; Bertol, Ildegardis; Fehlauer, Tercio Vaisnava (Scientia Agraria Paranaensis, 2020)
No-tillage is conservationist soil management for agricultural production and it is based on soil cover by crop residues and restricted mobilization to the sowing line. However, its structure can be affected by the excessive compaction resulting from the traffic of machines. The objective of this study was to evaluate soil physical properties and crop performance in no-tillage with and without scarification, combined with different successions of plant species, in a Humic Cambisol. For this, the species of black oat, wheat and forage turnip were cultivated in winter, and later, corn and beans in summer. Soil samples were collected at the beginning and at the end of the experimental period, while evaluations of plant yield were carried out in the final stage of development. Soil scarification reduces relative density (RD) and soil resistance to penetration (RP) after preparation of soil, with effect restricted to the surface layer. Such effects persist for one year, however RD and RP increase over time, regardless of soil management. RP is more sensitive for evaluation of soil compaction and correlates positively with RD, with exponential adjustment. The aerial biomass of black oat, wheat and forage turnip was not affected by soil scarification, and crop yield of beans and corn showed to be more related to the previous cultivation than the scarification in no-tillage.